Emotion Regulation: Potential Mediators of the Relationship Between Muraqabah and Academic Procrastination - Ulfanie Wiyatama; Lydia Freyani Hawadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Academic procrastination is a common problem in the world of education that harms students' educational activities. Muraqabah is considered to positively influence self-regulation, where emotion regulation is one of self-regulation' forms. Previous research has revealed that one of the efforts to overcome academic procrastination is to enhance the ability to regulate emotions. Excellent emotion regulation can change aversion emotions to reduce procrastination. This study investigates the relationship between academic procrastination, muraqabah, and emotion regulation. In addition, it also examines the role of emotion regulation as a mediator in the relationship between muraqabah and academic procrastination in Junior High School Students. Quantitative data were collected by distributing adaptation of the academic procrastination scale (APS), muraqabah questionnaire, and emotion regulation questionnaire (ERQ-CA). Participants in quantitative research were 201 students. This study showed a significant correlation in each pair of variables, and emotion regulation was found to significantly mediate the relationship between muraqabah and academic procrastination in junior high school students.